The Difference a Smile Makes: Effective Use of Imagery by Children's Nonprofit Organizations. Issue 3 (27th May 2019) - Jordan, Sara Rene; Rudeen, Stephanie; Hu, Deyu; Diotalevi, Jaina L.; Brown, Frederick I.; Miskovic, Phillip; Yang, HuiShan; Colonna, Meredith; Draper, Danielle
ABSTRACT: Which emotions are most appealing to donors in nonprofit outreach materials? Previous studies have shown that in print and television materials, images depicting negative emotions lead to increases in donor response. In this study, we examined whether images of negative affect in children in social media appeals lead to increased information sharing compared to positive or neutral images of children. We analyzed Facebook posts from 2016 from 2 large children's nongovernmental organizations, UNICEF USA and Save the Children US, and examined the relationship between the type of emotion in the image and the number of likes, comments, and shares that the post received. We found differences in the responses according to the organization sending the message and the affect of the children depicted. For Save the Children US, negative images, specifically sad and fearful images, generated significantly more likes, shares, and comments. For UNICEF USA, there was no difference in information sharing for positive, neutral, or negative images. Findings from this study demonstrate that negative emotional imagery of children can affect social media engagement with nongovernmental organizations, but this effect appears to be inconsistent.